Defining the neuroanatomic basis of motor coordination in children and its relationship with symptoms of attention-deficit/hyperactivity disorder. Issue 11 (10th June 2016) - Shaw, P.; Weingart, D.; Bonner, T.; Watson, B.; Park, M. T. M.; Sharp, W.; Lerch, J. P.; Chakravarty, M. M.
Abstract : Background: When children have marked problems with motor coordination, they often have problems with attention and impulse control. Here, we map the neuroanatomic substrate of motor coordination in childhood and ask whether this substrate differs in the presence of concurrent symptoms of attention-deficit/hyperactivity disorder (ADHD). Method: Participants were 226 children. All completed Diagnostic and Statistical Manual of Mental Disorders, fifth edition (DSM-5)-based assessment of ADHD symptoms and standardized tests of motor coordination skills assessing aiming/catching, manual dexterity and balance. Symptoms of developmental coordination disorder (DCD) were determined using parental questionnaires. Using 3 Tesla magnetic resonance data, four latent neuroanatomic variables (for the cerebral cortex, cerebellum, basal ganglia and thalamus) were extracted and mapped onto each motor coordination skill using partial least squares pathway modeling. Results: The motor coordination skill of aiming/catching was significantly linked to latent variables for both the cerebral cortex ( t = 4.31, p < 0.0001) and the cerebellum ( t = 2.31, p = 0.02). This effect was driven by the premotor/motor cortical regions and the superior cerebellar lobules. These links were not moderated by the severity of symptoms of inattention, hyperactivity and impulsivity. In categorical analyses, the DCD group showed atypical reduction in the volumes of these regions. However, the group with DCD alone did not differ significantly from those with DCD and co-morbid ADHD. Conclusions: The superior cerebellar lobules and the premotor/motor cortex emerged as pivotal neural substrates of motor coordination in children. The dimensions of these motor coordination regions did not differ significantly between those who had DCD, with or without co-morbid ADHD.